Relationship of Whitefly Population Build up with the Spread of TYLCV on Eight Tomato Varieties - Rahman, AHMA; Akanda, AM; Alam, AKM Ashraful (Journal of Agriculture & Rural Development, 2008)
The performance of eight tomato varieties namely BARI-T1 (Manik), BARI-T2 (Ratan), BARI-T4, BARI-T5, BARI-T6 (Apurba), BARI-T7 (Chaity), BARI-T11 and BARI-T12 were evaluated in respect to prevalence and spread of TYLCV (Tomato Yellow Leaf curl Virus) in relation to whitefly population buildup in the field. Data were collected on the three growth stages of the plant namely early (transplanting to first flowering) mid (first flowering to first harvesting) and late (first harvesting to last harvesting). The virus prevalence percentage in eight tomato varieties varied depending on early, mid and late stage of infection as well as tomato varieties. It ranged from 42 to 69%. There was a poor and insignificant quadratic polynomial relationship (y = -0.0059x 2 + 0.2826x 1.5378 & R2 = 0.0962) between temperature and whitefly population build up in tomato field. The relationship between relative humidity and whitefly population build up in the field was found significant but negatively correlated (y = - 0.0321x 2 +4.5518x 159.44 (R2 = 0.6769). The increase of whitefly population in the field was positively correlated with the spread of TYLCV in the tomato field (y = - 0.0002x 2 + 0.0297x + 1.0626 & R2 = 0.663). The highest and lowest prevalence of TYLCV was recorded in BARI-T6 and BARI-T11, respectively. In all the varieties, virus prevalence was found higher at mid stage followed by late and early stage of infection. Key words: Prevalence, TYLCV, whitefly.